Rethinking Obama - Go, Julian, 1970- (Political power and social theory,, 2011)
This volume of "Political Power and Social Theory" includes a selection of papers exploring Obama and the Politics of Race & Religion. Chapters examine the complex dynamics of race relations and racial meaning in America under the Obama administration. The "Scholarly Controversies" section features a debate on Obama and religion in the United States. This volume will be among the first to critically assess the meanings of race and religion in America under the Obama administration, featuring controversial chapters by Phil Gorksi of Yale University and Eduardo Bonilla-Silva of Duke University, among others.